Reviewing chemical and biological risks in urban agriculture: A comprehensive framework for a food safety assessment of city region food systems. (August 2021) - Buscaroli, E.; Braschi, I.; Cirillo, C.; Fargue-Lelièvre, A.; Modarelli, G.C.; Pennisi, G.; Righini, I.; Specht, K.; Orsini, F.
Abstract: Attention to urban agriculture (UA) has recently grown among practitioners, scientists, and the public, resulting in several initiatives worldwide. Despite the positive perception of modern UA and locally grown, fresh produce, the potential food safety risks connected to these practices may be underestimated, leading to regulatory gaps. Thus, there is a need for assessment tools to evaluate the food safety risks connected to specific UA initiatives, to assist practitioners in self-evaluation and control, and to provide policy makers and scholars a means to pursue and assess food safety in city regions, avoiding either a lack or an excess of regulation that could ultimately hinder the sector. To address this aim, this paper reviews the most recent and relevant literature on UA food safety assessments. Food safety indicators were identified first. Then, a food safety assessment framework for UA initiatives was developed. The framework uses business surveys and food analyses (if available) as a data source for calculating a food safety index for single UA businesses and the whole UA landscape of a given city region. The proposed framework was designed to allow its integration into the CRFS (City Region Food System) toolkit developed by FAO (Food and Agriculture Organization of the United Nations), RUAF foundation (Resource Centres on Urban Agriculture and Food Security) and Wilfrid Laurier University. Highlights: Connection of several biological and chemical food safety risks to UA techniques. Identifiable food safety risk factors for diverse UA practices. Framework for the assessment of food safety levels of UA initiatives. Development of a risk-based assessment that can be integrated into the FAO CRFS framework.